Efeitos de um programa de atenção diversificado às mães de alunos severamente prejudicados. - Martins, Morgana de Fátima Agostini (2006)
The national literature in the field of special education has continually pointed the necessity of research on programs towards attention to the families of persons with handicap. The present research start from the idea that diferent families can have diversified service necessities. This research was outlined to test this hypothesis, and the general objective of the study consisted in developping, evaluate and compare the efects of different contents of a program of attention to the mothers of the severaly handicapped. For the research was used an experimental delineation of multi elements baseline in which, 3 groups of mothers (A, B, C) was submitted to one sequency of three diferent contents in a attention program (Emotional Support S; Information I; and Training Abilities T), with variations in the order of offers of contents for each group. The study involved two stages, denominated as Study 1 and 2. Study 1 counted with the participation of 15 mothers of handicapped children from a special school and had as objectives: a) Identify the necessities of mothers with severelly handicapped children caracterizing aspects like received diagnostic, familiar structure, socialeconomic conditions and demographics, environment organization and routine, psicological conditions to establish gratefully interactions with their children. For this were done individualized interviews that later were tabulated and resulted in a survey of the necessities and potencialities of this mothers in relation to the child with deficiency. The results of this first stage was the identification of the potencialities and necessities of the families that were translated at the three contents for the attenction program and that allowed develop the program with the identified contents (Contents S, I, T). The study 2 had as participants 07 mothers of deficients students (with pre-school age, considered severally handicaped that attended a special school). For the implementation stage were done three groups, with the end to evaluate the efects of different presentation orders of the three contents about the following selected variables:- Comunnication Family-School CFE (measured by a note book); Adesion of the Family to the Service AFA (measured by school frequency registry of the children to the school) and about the development level of the students NDA, (measured by performance evaluations in seven areas of infantile development: cognition, socialization, nutrition, auto-care, motor abilities, courtesy rules and comunnication). The results pointed gains for all seven children at the development level, varying around 10 to 30% in all the areas for the majority of the children (6 in 7), reaching in some areas to 100% of the abilities. In relation to the variable CFE, the number of notes at the family book went from zero to 18 times, in three months, that was the duration time of the attention program. To the variable AFA, the frequency index at school varied from 80 to 100 % to all children. Is discussed at the end the necessity of implementing attention programs for families with children with defficiency, that been fundamented at the necessities of each family, starting with the hypothesis that families have diferent necessities, and that due this need diferent services. As far as the presentation order of contents, the data are suggestive that the most efficient order to the mothers os preschool children would be: Emotional support, information and training of abilities (SIT), to establish empathy and binding, followed by the information offer to increase the understanding about the deficiency, what would favour later on the trainning of abilities to the teaching of their children.